John Wansbrough dan Historisitas Alquran - Achmad Lutfi (JOURNAL OF QUR'AN AND HADITH STUDIES, 2018)
This paper discusses the historicity of the Quran in the view of John Wansbrough. By using the literature riview method, this study answers how Wansbrough views the historical aspects of the Quran. this study finds John Wansbrough addes another analytical consideration in understanding the history of the Quran. This is the application of the literary method which focuses on the analysis of the logic and the suitability of the use of language at the time of the revelation of the Quran.